Anthropometric and somatotype differences between C1 paddlers who were and were not selected for the Czech national team - Jan Busta; Ivana Kinkorová; James Joseph Tufano; Milan Bílý; Jiří Suchý (Karolinum Press, 2018)
The objective of this study was to determine the anthropometric and somatotype differences between elite single-canoeists (C1) included in the white-water slalom Czech national team (NT) (n = 5) and others (n = 12) who did not qualify for the national team (DNQ) leading up to the Olympic Games in Rio de Janiero, 2016. All paddlers were measured using a battery of 40 anthropometric parameters in one day, 4 weeks before competing in the Czech national selection races. The NT racers had a significantly (p < 0.05) greater circumference of the forearm (27.8 ± 0.6 vs. 26.8 ± 1.4) and upper arm (35.60 ± 1.5 vs. 33.5 ± 1.7) for the dominant paddling arm, as well as a greater chest circumference (98.3 ± 2.4 vs. 93.9 ± 2.3). Additionally, the sum of triceps, scapular, calf, and supraspinal skinfolds were significantly less in NT. There were no significant differences in height (p = 0.14), body mass (p = 0.18) or circumferences of the lower extremities (p = 0.09-0.32). Somatotype was statistically similar (p = 0.06-0.13), but practically different (NT = 1.4-5.6-2.3; DNQ = 1.6-4.6-3.1) such as body fat percentage (NT = 7.5 ± 2.3; DNQ = 9.1 ± 1.6). Based on the results of this study we can recommend that single-canoeists seeking to achieve elite performance should participate in training that focuses on maximizing the musculature of the upper limbs and chest while maintaining minimal body fat. The current data also shows that experience likely plays a role in national team selection, as NT were an average of 5.5 years older than DNQ.